PENGEMBANGAN E-MODUL TITRASI ASAM BASA BERBASIS BLENDED LEARNING DENGAN APLIKASI KVISOFT FLIPBOOK MAKER - Nurhayani Nurhayani; Ramlan Silaban; Moondra Zubir (PROSIDING SEMINAR KIMIA, 2022)
This study aims to determine the expert team's assessment of acid-base titration e-module based on blended learning with the kvisoft flipbook maker application by BSNP (Badan Standar Nasional Pendidikan). The research type used is research and development modified from development ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model. This research is only used until product validation. The data sources in this research were 2 expert validators. The results showed that the expert team's assessment of the acid-base titration e-module based blended learning with the kvisoft flipbook maker application by BSNP on the aspect content feasibility had an average percentage value of 86%, language feasibility of 88%, and presentation feasibility analysis of 85% and concluded that the media was very feasible to use and didn’t need to be revised. Keywords: E-module, acid-base titration, blended learning, kvisoft flipbook maker